Bile Acid–Microbiome Interaction Promotes Gastric Carcinogenesis (Adv. Sci. 16/2022). Issue 16 (3rd June 2022) - Wang, Shouli; Kuang, Junliang; Zhang, Hongwei; Chen, Wenlian; Zheng, Xiaojiao; Wang, Jieyi; Huang, Fengjie; Ge, Kun; Li, Mengci; Zhao, Mingliang; Rajani, Cynthia; Zhu, Jinshui; et al.
Abstract : New Strategy for the Prevention of Gastric Cancer Bile reflux can promote gastric carcinogenesis through activation of the IL‐6/JAK1‐STAT3 signaling pathway. Inhibition of STAT3 by cryptotanshinone can alleviate this carcinogenic effect, thus providing a new strategy for the prevention of gastric cancer associated with bile reflux. More details can be found in article number 2200263 by Aihua Zhao, Wei Jia, and co‐workers.